Characterizing Subsurface Structures From Hard and Soft Data With Multiple‐Condition Fusion Neural Network - Cui, Zhesi; Chen, Qiyu; Luo, Jian; Ma, Xiaogang; Liu, Gang (Water resources research, 2024)
Accurately inferring realistic subsurface structures poses a considerable challenge due to the impact of morphology on flow and transport behaviors. Traditional subsurface characterization relies on two primary types of data: hard data, derived from direct subsurface measurements, and soft data, encompassing remotely sensed geophysical information and its interpretation. Existing deep‐learning‐based methodologies predominantly focus on the transition from multiple observations to subsurface structures. However, implicit non‐linear correlations among diverse data sources often remain underutilized, leading to potential bias and errors. In this study, we introduce a multiple‐condition fusion network (MCF‐Net) to characterize subsurface structures based on both hard and soft data. To harness the full potential of multiple‐source subsurface observations, two distinct neural networks extract implicit features from hard and soft data. The integration of these features is achieved through multiple‐condition fusion blocks, designed to capture representative characteristics. These blocks are also adept at reconstructing heterogeneous structures and facilitating hydrological parameterization. MCF‐Net exhibits accuracy in estimating subsurface structures across various types of subsurface observations. Experimental results underscore the utility and superiority of MCF‐Net in applications of hydrogeological modeling. Key Points A novel approach for describing complex subsurface structures using sparse observations (hard data) and auxiliary variables (soft data) The proposed deep learning network is able to establish the implicit relationship among multiple observations The proposed approach can be easily extended and widely used for reservoir characterization, hydrogeophysical modeling, and other fields